G7 currencies in the oil storm: A deep dive into shock responses - Gainetdinova, Anna (2026)
G7 countries accounted for approximately 53% of the world's petroleum consumption; thus, shocks to the oil market have significant economic implications. To this end, we investigate the responses of G7 real effective exchange rates (REERs) to oil supply, demand, and risk shocks across various economic circumstances. Given the high fluctuations of oil markets over our sample period (from February 28, 2013, to March 14, 2023), we apply the cross-quantilogram approach to measure the fat-tailed linkage between oil shocks and REER. Our results demonstrate that G7 REERs are highly exposed to oil demand shocks while being least exposed to oil supply shocks. The REER of Canada encounters a depreciation in response to the supply and risk shocks, while that of the UK experiences a depreciation in response to supply and demand shocks in the long memory. Additionally, we find that REERs of Italy, Japan, the US, and Germany are less exposed to oil market shocks. Our findings are robust considering the rolling-window-based cross-quantilogram that accounts for bearish, normal, and bullish market conditions.